An assessment of early Child Life Therapy pain and anxiety management: A prospective randomised controlled trial. Issue 8 (December 2015) - Hyland, Ela J.; D'Cruz, Rachel; Harvey, John G.; Moir, Jordyn; Parkinson, Christina; Holland, Andrew J.A.
Highlights: Distraction remains useful in reducing pain and anxiety. Pain and anxiety from burn dressings has negative effects. Child Life Therapy was beneficial in reducing pain. Child Life Therapy had no observed impact on anxiety. Abstract: Introduction: Burns remain extremely painful and distressing in young children. The consequences of poorly managed pain and anxiety can be life-long. Whilst Child Life Therapy (CLT) has been shown to be effective in many situations, few studies have looked at the effectiveness of CLT in regard to reducing pain and anxiety in children undergoing burn dressing changes. Methods: A prospective, randomised controlled trial was conducted, comparing CLT versus standard care in relation to pain and anxiety scores of children undergoing their initial burn dressing change. Pain and anxiety were assessed by an independent observer and questionnaires completed by the child, parent/caregiver and nursing staff. Results: 50 subjects were recruited in each treatment group; median age 2.3 years (CLT) and 2.2 years (standard care). The median total body surface area (TBSA) burnt was 0.8% (CLT) and 0.5% (standard care). The majority were partial thickness dermal burns (88% CLT, 94% standard care). Rates of parent anxiety and pre-procedural child pain and anxiety were similar. Combined and scaled pain and anxiety scores in the CLT group were significantly less than in the standard treatment group ( p  =  0.03 ). Whilst pain was significantly better in the CLT group ( p  =  0.02 ), fear scores, wound outcomes and the need for skin grafting were not statistically different in either group. Conclusions: The presence of a Child Life Therapist, with their ability to adapt to the environment, the child and their family, significantly reduced the experience of pain during paediatric burn dressings.